2013
DOI: 10.1037/a0033111
|View full text |Cite
|
Sign up to set email alerts
|

Negative social comparison on Facebook and depressive symptoms: Rumination as a mechanism.

Abstract: Recent research demonstrates that it is the quality rather than the frequency of social networking experiences that places individuals at risk for negative mental health outcomes. However, the mechanisms that account for this association have yet to be examined. Accordingly, this study examined whether the tendency to negatively compare oneself with others while using Facebook leads to increases in depressive symptoms, and whether this association is mediated by increases in rumination. A sample of 268 college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
275
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(307 citation statements)
references
References 44 publications
(57 reference statements)
22
275
1
9
Order By: Relevance
“…26 In terms of frequency, positive correlations were found between depression and Facebook addiction or pathological SNS use, 23,42,43 and Facebook intrusion, 44 although conversely one study found a negative correlation between depression and addictive SNS use. 30 In relation to type of online social networking behaviour, positive correlations were found between Facebook impression management, 32 envy triggered by Facebook surveillance, 31 accepting former partners' invitations to become Facebook friends, 45 producing more content or engaging in greater interactive communication on Facebook, 46 social comparison with others, 39,47 and frequent negative status updates or negative comparison with others leading to increased rumination. 39,48 In contrast, negative correlations were found between depression and location tagging, 28 and frequent posting of positive Facebook status updates leading to reduced rumination.…”
Section: !mentioning
confidence: 99%
“…26 In terms of frequency, positive correlations were found between depression and Facebook addiction or pathological SNS use, 23,42,43 and Facebook intrusion, 44 although conversely one study found a negative correlation between depression and addictive SNS use. 30 In relation to type of online social networking behaviour, positive correlations were found between Facebook impression management, 32 envy triggered by Facebook surveillance, 31 accepting former partners' invitations to become Facebook friends, 45 producing more content or engaging in greater interactive communication on Facebook, 46 social comparison with others, 39,47 and frequent negative status updates or negative comparison with others leading to increased rumination. 39,48 In contrast, negative correlations were found between depression and location tagging, 28 and frequent posting of positive Facebook status updates leading to reduced rumination.…”
Section: !mentioning
confidence: 99%
“…The negative effects of general social media use on mood (Appel et al, 2016;Chou & Edge, 2012;Feinstein et al, 2013) have been attributed to the positivity bias on social media, that is, people's ability and tendency to present the most positive sides of themselves and their lives on these platforms (Lin & Utz, 2015;Qiu et al, 2012;Reinecke & Trepte, 2014). The current study tests if exposure to positively biased Instagram posts from strangers has consequences for positive and negative affect relative to viewing no posts or neutral posts by the same strangers.…”
Section: Social Comparisonmentioning
confidence: 99%
“…In survey research among college-aged young adults, social media use was positively related to the belief that others are better off (Chou & Edge, 2012;de Vries & Kühne, 2015). The belief that others are better off, in turn, was negatively related to emotional wellbeing (Feinstein et al, 2013). Furthermore, crosssectional, prospective, and experience sampling research has shown that Facebook use is related to the negative emotion envy (for a review see Appel et al, 2016).…”
Section: Social Comparisonmentioning
confidence: 99%
“…are prone to present an idealized self. When this happens on Facebook, it can lead to negative affect [21,47] and has even been linked to depression [23].…”
Section: The Perfect Familymentioning
confidence: 99%